PEMBELAJARAN TEKS BIOGRAFI KELAS X SMA NEGERI 1 MEMPAWAH HILIR - Rahmadhanti, Diah; Martono, Martono; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to analyze the implementation of the independent curriculum in the learning of biography texts in class X C SMA Negeri 1 Mempawah Hilir. The method used is descriptive to explain the planning, implementation, and learning outcomes analyzed using the Teacher Performance Supervision Tool (APKG) 1 and 2. The subjects of this study are Indonesian teachers of class X, Mrs. Dewi Setiyani, S.Pd and students of class X C SMA Negeri 1 Mempawah Hilir totaling 36 people. The data obtained is the result of planning analysis in the form of a teaching module made by teachers using APKG 1 which got a score of 69 (Less), the implementation of learning was analyzed using APKG 2, the score of the first meeting was 81.6 (Good) and the second meeting was 66.3 (Poor). The learning results of students showed that half of the students in the class were above KKTP. The learning outcomes of students showed that half of the students in the class got a score above the KKTP. In the attitude assessment, teachers used 4 out of 6 Pancasila Student Profiles (P3), knowledge there were 21 people who got a score above KKTP and 12 people below KKTP, and skills as many as 20 people above KKTP, 6 people equivalent to KKTP, and 6 people under KKTP.